Leadership Transformational Head School in Increase Quality Education - Helik Sudiono; Mohamad Muspawi (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this study is to determine the leadership used in increase And develop quality education . Method Which used in research this is qualitative methods that is with approach case study Which Where Researchers go directly into the field with the aim of observing phenomena or problems. any problems Which happened at the school. problem Which at the beginning take office as head school is in increase quality education. A problems that need to be solved or overcome . impact resolution positive the followed by public around including person old. Results study show that, Head School use leadership Transformational. In matter This Head School can change And increase quality education